Quality of life and coping strategies used by parents of children with autism spectrum disorder in Oman. (November 2022) - ALBusaidi, Alya Mohammed Said; ALMasroori, Salima Ali Saud; Awladthani, Balqees Mohammed Said; ALKhaldi, Sumaiya Abdullah; Al Alawi, Noof; Al Salmani, Asma Ali
Objective: Raising a child with autism spectrum disorder (ASD) can have a significant impact on quality of life (QOL). This study was conducted to assess the QOL and coping strategies of parents of children with ASD in Oman. Method: This descriptive cross-sectional study was conducted at Al-Masarra psychiatric hospital. Telephone interviews were conducted with the parents of all children diagnosed with ASD and attending Al-Masarra Hospital between January 2018 and October 2021. Data were collected using the Ways of Coping Checklist-Revised and World Health Organization Quality of Life Assessment-Brief. Results: A total of 304 parents participated in the study (response rate: 100%), of which 59.5% were female. The mean age of the parents and children with ASD was 40.4 ± 6.9 and 8.4 ± 2.3 years, respectively. Most children with ASD were male (78.3%) and entirely dependent upon their parents (18.1%). Seeking social support was the most common coping strategy (75.53 ± 13.99), while escape avoidance was the least common (51.78 ± 8.04). Most parents (48.7%) rated their QOL as good to very good, with acceptable scores in the psychological (70.92 ± 11.22) and social (73.27 ± 11.46) domains, borderline in the physical health domain (63.51 ± 7.77), and poor in the environmental domain (58.31 ± 11.00). Conclusions: Omani parents of children with ASD utilize various coping strategies, with coping skills considered a positive index for mental health in general. No significant differences were observed between Omani fathers and mothers in terms of QOL or coping strategies.